Recombinant thrombomodulin attenuates hyper-inflammation and glycocalyx damage in a murine model of Streptococcus pneumoniae–induced sepsis. (January 2022) - Watanabe, Eizo; Akamatsu, Toshinobu; Ohmori, Masaaki; Kato, Mayu; Takeuchi, Noriko; Ishiwada, Naruhiko; Nishimura, Rintaro; Hishiki, Haruka; Fujimura, Lisa; Ito, Chizuru; Hatano, Masahiko
Highlights: Serum TNF-α was reduced after intratracheal injection in S. pneumoniae –challenged mice treated with rTM. Lung endothelial IL-10 expression increased after intratracheal injection in S. pneumoniae –challenged mice treated with rTM. rTM modulates local inflammation in the lung endothelium, thus diminishing systemic inflammation. Serum syndecan-1 levels decreased in rTM-treated mice after intratracheal injection of S. pneumoniae . rTM treatment preserved the morphology of the glycocalyx layer in S. pneumoniae –challenged mice. Abstract: Purpose: The anticoagulant agent recombinant thrombomodulin (rTM) activates protein C to prevent excessive coagulation and also possibly regulates hyper-inflammation via neutralization of high-mobility-group B1 (HMG-B1). The glycocalyx layer in endothelial cells also plays a pivotal role in preventing septic shock–associated hyperpermeability. The present study examined the effect of rTM in a murine model of Streptococcus pneumoniae –induced sepsis. Methods: Male C57BL/6N mice were injected intratracheally via midline cervical incision with 2 × 10 7 CFU of S. pneumoniae (capsular subtype 19A). Control mice were sham-treated identically but injected with saline. rTM (10 mg/kg) was injected intraperitoneally 3 h after septic insult. Blood concentrations of soluble inflammatory mediators (interleukin [IL]-1β, IL-6, IL-10, and tumor necrosis factor [TNF]-α) were determined using a microarray immunoassay. Serum concentrations of HMG-B1 and syndecan-1, as a parameter of glycocalyx damage, were determined by enzyme-linked immunosorbent assay. The glycocalyx was also evaluated with electron microscopy. The lungs were removed, and digested to cells, which were then stained with a mixture of fluorophore-conjugated antibodies. Anti-mouse primary antibodies included PE-Cy7–conjugated anti-CD31, AlexaFluor 700–conjugated anti-CD45, PerCP-Cy5.5–conjugated anti-CD326, APC-conjugated anti–TNF-α, PE-conjugated anti–IL-6, and PE-conjugated anti–IL-10. A total of 1 × 10 6 cells per sample were analyzed, and 2 × 10 5 events were recorded by flow cytometry, and parameters were compared with/without rTM treatment. Results: The blood concentration of TNF-α was significantly reduced 24 h after intratracheal injection in S. pneumoniae –challenged mice treated with rTM ( P = 0.016). Levels of IL-10 in the lung endothelium of rTM-treated S. pneumoniae –challenged mice increased significantly 12 h after intratracheal injection ( P = 0.03). Intriguingly, serum HMGB-1 and syndecan-1 levels decreased significantly ( P = 0.010 and 0.015, respectively) in rTM-treated mice 24 h after intratracheal injection of S. pneumoniae . Electron microscopy indicated that rTM treatment preserved the morphology of the glycocalyx layer in septic mice. Conclusions: These data suggest that rTM modulates local inflammation in the lung endothelium, thus diminishing systemic inflammation, i.e., hypercytokinemia. Furthermore, rTM treatment reduced serum syndecan-1 levels, thus preventing glycocalyx damage. The use of rTM to treat sepsis caused by bacterial pneumonia could therefore help prevent both excessive inflammation and glycocalyx injury in the lung endothelium.